2000
DOI: 10.1074/jbc.c000409200
|View full text |Cite
|
Sign up to set email alerts
|

XIST RNA Associates with Specific Regions of the Inactive X Chromatin

Abstract: Microscopy studies have shown that XIST RNA colocalizes with the inactive X chromosome (Xi). However, the molecular basis for this colocalization is unknown. Here we provide two lines of evidence from chromatin immunoprecipitation experiments that XIST RNA physically associates with the Xi chromatin. First, XIST RNA can be co-precipitated by antiserum against macroH2A, a histone H2A variant enriched in the Xi. Second, XIST RNA can be co-precipitated by antisera that recognize unacetylated, but not acetylated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…It has been found that inactive X chromosomes in mouse cells have elevated levels of a specific histone isoform, macroH2A1.2, suggesting that this histone variant might be an effector of the silencing process [20]. This idea is supported by the observation that Xist RNA and macroH2A1.2 can form a stable ribonucleoprotein complex [21] and that the localization of macroH2A1.2 in X-chromosome chromatin depends on the expression of Xist [22]. The function of Xist RNA may be to recruit macroH2A1.2 so as to establish and maintain an inactive state [18].…”
Section: Dosage Compensationsupporting
confidence: 66%
“…It has been found that inactive X chromosomes in mouse cells have elevated levels of a specific histone isoform, macroH2A1.2, suggesting that this histone variant might be an effector of the silencing process [20]. This idea is supported by the observation that Xist RNA and macroH2A1.2 can form a stable ribonucleoprotein complex [21] and that the localization of macroH2A1.2 in X-chromosome chromatin depends on the expression of Xist [22]. The function of Xist RNA may be to recruit macroH2A1.2 so as to establish and maintain an inactive state [18].…”
Section: Dosage Compensationsupporting
confidence: 66%
“…Indeed, HEK293 are female cells with an atypical karyotype, usually containing 3 X chromosomes, 2 of which are inactive and visible as large heterochromatic bodies (18). Through FISH, using as a probe the X-inactive specific transcript (XIST), an untranslated RNA that coats the Xi (18,19) we confirmed that exogenous BAHD1 was recruited at these 2 Xi . V5-or YFP-BAHD1 localized at the 2 Xi in HEK293 cells (Figs.…”
Section: Ectopically Expressed Bahd1 Colocalizes With Histone H3k27me3mentioning
confidence: 49%
“…RNA Immunoprecipitation-RNA immunoprecipitation was carried out as described previously with slight modifications (30). HEK293 cells were trypsinized, washed twice with PBS, and resuspended in 10 ml of PBS.…”
Section: Methodsmentioning
confidence: 99%